Insecticide resistance status and mechanisms in Aedes aegypti and Aedes albopictus from different dengue endemic regions of Panama - Lorenzo Cáceres Carrera; Luis Piedra; Rolando Torres-Cosme; Anakena M. Castillo; Antonio Bruno; José Luis Ramírez; Dan Martínez; María Magdalena Rodríguez; Juan A. Bisset (Tropical Medicine and Health, 2024)
Abstract Background Dengue is a serious public health problem worldwide, including Panama. During the last years, the number of dengue cases has increased. This may be due to the presence of mosquito populations resistant to insecticides. The aim of this study was to characterize the resistance status, its enzymatic mechanisms and Kdr mutations in wild populations of Aedes aegypti and Aedes albopictus. Methods Standard WHO bioassays were performed using insecticide-treated filter papers to determine resistance in populations Ae. aegypti and Ae. albopictus to pyrethroids insecticides, organophosphates, to the carbamate propoxur and to the organochlorine DDT. Biochemical assays were conducted to detect metabolic resistance mechanisms and real-time PCR was performed to determine the frequencies of the Kdr mutations Val1016IIe and F1534C. Results The strains Ae. aegypti El Coco showed confirmed resistance to deltamethrin (78.5% mortality) and lambda-cyhalothrin (81%), Aguadulce to deltamethrin (79.3%), David to deltamethrin (74.8%) and lambda-cyhalothrin (87.5%) and Puerto Armuelles to permethrin (83%). Aedes aegypti El Empalme showed confirmed resistance to pirimiphos-methyl (62.3% mortality), chlorpyrifos-methyl (55.5%) and propoxur (85.3%). All strains of Ae. albopictus showed possible resistance to PYs and five strains to DDT. Only Ae. albopictus Canto del Llano showed confirmed resistance to pirimiphos-methyl (70% mortality) and malathion (62%). Esterase activity was variable across sites with the most frequent expression of α-EST compared to β-EST in Ae. aegypti populations. In Ae. Albopictus, the expressed enzymes were β-EST and MFOs. Through ANOVA, significant differences were established in the levels of enzymatic activity of α- and β-EST, MFOs and GST, with p < 0.001 in the Ae. aegypti and Ae. albopictus. The Kdr Val1016IIe mutation was detected in Ae. aegypti Aguadulce, El Coco and David. The odds ratio for the Val1016Ile mutation ranged from 0.8 to 20.8 in resistant mosquitoes, indicating the association between pyrethroid phenotypic resistance and the kdr mutation. Conclusion The presence of a varied and generalized resistance, enzymatic mechanisms and the Val1016IIe mutation may be associated with the intensive use and possibly misuse of the different insecticides applied to control Aedes populations. These results highlight the need to develop a program for resistance management. Also, alternative approaches to mosquito control that do not involve insecticides should be explored.